Induction of Pluripotent Stem Cells from a Manifesting Carrier of Duchenne Muscular Dystrophy and Characterization of Their X-Inactivation Status - Yuko Miyagoe-Suzuki; Takashi Nishiyama; Miho Nakamura; Asako Narita; Fusako Takemura; Satoru Masuda; Narihiro Minami; Kumiko Murayama; Hirofumi Komaki; Yu-ichi Goto; Shin’ichi Takeda (Stem Cells International)
Three to eight percent of female carriers of Duchenne muscular dystrophy (DMD) develop dystrophic symptoms ranging from mild muscle weakness to a rapidly progressive DMD-like muscular dystrophy due to skewed inactivation of X chromosomes during early development. Here, we generated human induced pluripotent stem cells (hiPSCs) from a manifesting female carrier using retroviral or Sendai viral (SeV) vectors and determined their X-inactivation status. Although manifesting carrier-derived iPS cells showed normal expression of human embryonic stem cell markers and formed well-differentiated teratomas in vivo, many hiPS clones showed bi-allelic expression of the androgen receptor (AR) gene and loss of X-inactivation-specific transcript and trimethyl-histone H3 (Lys27) signals on X chromosomes, suggesting that both X chromosomes of the hiPS cells are in an active state. Importantly, normal dystrophin was expressed in multinucleated myotubes differentiated from a manifesting carrier of DMD-hiPS cells with XaXa pattern. AR transcripts were also equally transcribed from both alleles in induced myotubes. Our results indicated that the inactivated X chromosome in the patient’s fibroblasts was activated during reprogramming, and XCI occurred randomly during differentiation.